DEVELOPMENT AND EVALUATION OF BILAYER TABLETS FOR IMMEDIATE AND CONTROLLED RELEASE OF METFORMIN HYDROCHLORIDE - Saikia, Rablee; Sahu, Bhanu Pratap (International Journal of Current Pharmaceutical Research, 2017)
Objective: The purpose of this study was to develop and evaluate bi-layer tablets for the immediate and controlled release of Metformin Hydrochloride for effective treatment of type 2 Diabetes mellitus. Methods: The immediate release layer was prepared by using super disintegrants like cross carmellose sodium, sodium starch glycolate and sustained release layer was prepared by using hydrophilic polymer like HPMC K 100 and PVP. Various proportions of super disintegrants and polymer were used to select the best formulation composition. Bilayer tablet of metformin was prepared by wet granulation method and was evaluated for physical characteristics like hardness, weight variation, and friability. In vitro release of drug was performed in USP type II dissolution test apparatus using phosphate buffer (pH 6.8) as dissolution media and dissolution was continued for 9 h for the sustained release layer. For immediate release layer, readings were recorded in each 10 min time interval for the first 1h. Results: From the obtained result it was found that all the formulations were within the limit of the standard. The hardness was found to be in the ranges from 5.1 to 5.5 kg/cm2, weight variation was in the range 0.53% to 0.83%, friability of all the formulations was within the range (<1%)and percentage of drug content was more than 97%. The drug release of the tablet was in the range of 85%-91% in 9 h. Conclusion: From the result obtained, it is found that the formulation F6 satisfies all the criteria as sustained release tablet for the effective treatment of type 2Diabetes mellitus.